A Systematic Literature Review of Authentication in Internet of Things for Heterogeneous Devices - Sanaz Kavianpour; Bharanidharan Shanmugam; Sami Azam; Mazdak Zamani; Ganthan Narayana Samy; Friso De Boer (Journal of Computer Networks and Communications)
Internet of Things (IoT) has become one of the most significant technologies in recent years because of possessing the diverse application domains. The variety of applications results in a large amount of users’ private information diffusion that will pose a paramount security concern. User authentication is a significant factor in the IoT environment as it allows the user to communicate with the device securely. Integration of authentication technologies with IoT ensures secure data retrieval and robust access control. This paper provides a comprehensive systematic literature review of various authentication mechanisms for IoT security proposed in the literature. With the comparison of existing authentication mechanisms that are developed for the IoT in terms of security via a multicriteria classification, the open issues that require further research are identified.